Penerapan Metode 3M (Mewarnai, Memotong, Menempel) untuk Meningkatkan Motorik Halus Anak Tunagrahita Ringan Kelas 3C SLB Manunggal Slawi - Amelia Zulfal Asvia; Faizah Muawanah; Fajar Muzaki Mustofa; Ghina Rahma Izzati; Efvelin BS ((JPAP) Jurnal Praktisi Administrasi Pendidikan, 2026)
Fine motor skills are an important aspect in the development of children with mild intellectual disabilities because they directly affect functional independence, basic academic abilities, and readiness to carry out daily activities. This study aims to describe the effectiveness of applying the 3M Method (Coloring, Cutting, Pasting) in improving the fine motor skills of mildly mentally disabled students in class 3C at SLB Manunggal Slawi. The study used a classroom action research (CAR) design with a descriptive qualitative approach conducted in two cycles. The research subjects consisted of six students in class 3C, while the teacher acted as a facilitator in each stage of the action. Data collection techniques included participatory observation and documentation of student work on each 3M activity. The results showed that in Cycle I, students began to show enthusiasm, but there were still various obstacles, such as inaccuracy when coloring outside the lines and a lack of precision when cutting patterns. After implementing strategic improvements and more intensive guidance in Cycle II, students' fine motor skills showed significant improvement. This was evident in neater coloring skills, improved cutting accuracy, and more focused and instruction-compliant pasting abilities. Thus, it can be concluded that the 3M Method has proven effective in stimulating eye-hand coordination, strengthening fine motor control, and gradually and systematically improving the fine motor skills of children with mild intellectual disabilities.